2022
DOI: 10.3389/fsurg.2022.945013
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy-assisted partial trapeziectomy combined with ligament reconstruction for thumb carpometacarpal joint osteoarthritis: A different technique

Abstract: BackgroundThere is no consensus on the best surgery option for thumb carpometacarpal osteoarthritis (CMC OA). The traditional method has the risk of large trauma, obvious metacarpal subsidence, and decreased stability. The aim of this study is to introduce a different technique to restore the function and stability of the first carpal metacarpal joint with minimal trauma, rapid pain relief, reduced complications, and the clinical outcomes in the long-term follow-up was evaluated and statistically analyzed.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…However, the mean follow-up duration was 15 months for the AD group and 14 months for the TRAP group. The present study demonstrates that at longer follow-up durations, up to 81.6 months in the AD group and 46.6 months in the TRAP group, there are insignificant changes in pain scores postoperatively between the two procedures [ 25 , 30 ]. This observation suggests that while TRAP may offer superior short-term pain relief, the long-term efficacy in terms of pain reduction appears to converge between the two treatments.…”
Section: Reviewmentioning
confidence: 89%
See 3 more Smart Citations
“…However, the mean follow-up duration was 15 months for the AD group and 14 months for the TRAP group. The present study demonstrates that at longer follow-up durations, up to 81.6 months in the AD group and 46.6 months in the TRAP group, there are insignificant changes in pain scores postoperatively between the two procedures [ 25 , 30 ]. This observation suggests that while TRAP may offer superior short-term pain relief, the long-term efficacy in terms of pain reduction appears to converge between the two treatments.…”
Section: Reviewmentioning
confidence: 89%
“…This indicates clinically significant pain reduction, even though initial pain levels were mild across different stages of arthritis [ 27 ]. Zheng et al reported 10 patients with mixed stages of arthritis and substantial pain relief from an average of 6.4 preoperatively to 1.1 postoperatively [ 30 ]. However, Pereira et al’s study contradicted the above arthroscopy results with a high failure rate and conversion to TRAP when arthroscopic intervention was done in the advanced stages of arthritis [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations